2013
DOI: 10.1530/rep-12-0219
|View full text |Cite
|
Sign up to set email alerts
|

The roles of glial cell line-derived neurotrophic factor, brain-derived neurotrophic factor and nerve growth factor during the final stage of folliculogenesis: a focus on oocyte maturation

Abstract: Neurotrophic factors were first identified to promote the growth, survival or differentiation of neurons and have also been associated with the early stages of ovarian folliculogenesis. More recently, their effects on the final stage of follicular development, including oocyte maturation and early embryonic development, have been reported. Glial cell line-derived neurotrophic factor (GDNF), brain-derived neurotrophic factor (BDNF) and nerve growth factor (NGF), which are expressed in numerous peripheral tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 93 publications
(150 reference statements)
1
26
0
Order By: Relevance
“…Many of the signaling pathways overrepresented by these targets corresponded to growth factors putatively involved in follicular cell proliferation and steroidogenesis and prevention of premature luteinization including HGF, IGF1, TGFb, estrogen, neurotropin/TRK, PEDF, and NGF (Parrott et al 1993, Salas et al 2006, Glister et al 2010, Mani et al 2010, Garcia-Rudaz et al 2011, Chuderland et al 2013 and others involved in oocyte maturation including neuregulin, GDNF, and EGF (Conti et al 2006, Noma et al 2011, Linher-Melville & Li 2013, the fine-tune regulation of which is of key importance during the final stages of follicle development. Also present were several core cell cycle regulatory pathways (cell cycle regulation by BTG family proteins, estrogen-mediated S phase entry, and G1/S checkpoint regulation), a finding which is consistent with the notion that the development of the dominant follicle involves a substantial decrease in granulosa cell proliferation (Lussier et al 1987, Gaytan et al 1996.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the signaling pathways overrepresented by these targets corresponded to growth factors putatively involved in follicular cell proliferation and steroidogenesis and prevention of premature luteinization including HGF, IGF1, TGFb, estrogen, neurotropin/TRK, PEDF, and NGF (Parrott et al 1993, Salas et al 2006, Glister et al 2010, Mani et al 2010, Garcia-Rudaz et al 2011, Chuderland et al 2013 and others involved in oocyte maturation including neuregulin, GDNF, and EGF (Conti et al 2006, Noma et al 2011, Linher-Melville & Li 2013, the fine-tune regulation of which is of key importance during the final stages of follicle development. Also present were several core cell cycle regulatory pathways (cell cycle regulation by BTG family proteins, estrogen-mediated S phase entry, and G1/S checkpoint regulation), a finding which is consistent with the notion that the development of the dominant follicle involves a substantial decrease in granulosa cell proliferation (Lussier et al 1987, Gaytan et al 1996.…”
Section: Discussionmentioning
confidence: 99%
“…It has been hypothesized that the restorative effects of MSCs transplantation on impaired ovarian function resulted from secretion of trophic factors, which are beneficial to follicle growth [9], [10]. Previous studies reported that AFSCs can secrete TGF-β [51], vascular endothelial growth factor [52], and glia cell-derived neurotrophic factor [53], which are required for follicular development [54], [55], and can inhibit follicular cell apoptosis [56] and follicle atresia [57]. Taken together, we infer that the favorable effects of AFSCs on CTx-damaged ovary is derived from the paracrine secretion of certain beneficial factors, which support ovarian follicle survival.…”
Section: Discussionmentioning
confidence: 99%
“…NGF has also been recognized as such an ovarian factor [10]. It was identified in the ovary of several species, including the human [11], in which also the pertinent receptors p75 NTR and TrkA were found [12, 13].…”
Section: Introductionmentioning
confidence: 99%